The Undercount of Young Children in the U.S. Decennial Census - OHare, William (Springer, 2015)
This book covers several dimensions of the undercount of young children in the U.S. Decennial Census, examines the data from the 2010 U.S. Decennial Census in detail and looks at trends in the undercount of children over time. Other aspects included are the geographic distribution of the net undercount and an exploration for some of the potential explanations for the high net undercount of children. The number of young children in the US is growing, but almost one million young children (under age 5) were missed in the 2010 U.S. Decennial Census. The net undercount of young children has been higher than any other age group for the past several decades and is increasing rapidly, but little attention has been paid to the issue but demographers or the public.